2009
DOI: 10.1159/000224656
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility of Extended-Spectrum Beta-Lactamase-Producing Bacteria in Intensive Care Units of Sanandaj General Hospitals (Kurdistan, Iran)

Abstract: This study focused on analyzing the spread of extended-spectrum β-lactamase (ESBL) enzymes among Gram-negative bacteria at intensive care units (ICUs). Between January 2007 and January 2008, 301 consecutive clinical isolates of Gram-negative type were isolated. Of these, 66 strains were collected from patients in ICUs in two major hospitals in Sanandaj (Kurdistan, Iran). The isolates were identified, tested for antimicrobial susceptibility, and analyzed for the presence of ESBL using the double-disk synergy te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…DISCUSSION β-lactamase-producing K. pneumoniae was first identified in 1983 21 . Most infections caused by K. pneumoniae are due to multi-drug resistant strains such as β-lactamase producing isolates 22 . Recent studies have shown that the incidence of β-lactamase-producing K. pneumoniae is increasing in several countries such as Iran 22,23 , India 24,25 , and Italy…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION β-lactamase-producing K. pneumoniae was first identified in 1983 21 . Most infections caused by K. pneumoniae are due to multi-drug resistant strains such as β-lactamase producing isolates 22 . Recent studies have shown that the incidence of β-lactamase-producing K. pneumoniae is increasing in several countries such as Iran 22,23 , India 24,25 , and Italy…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms of resistance to cefepime include the production of extended-spectrum β-lactamases and metalloenzymes, which hydrolyze cefepime [14,15,16]. These enzymes can spread within the community and in hospitals [17,18,19,20]. Therefore, cefepime-resistant pathogens are a major threat to infection treatment and control programs.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, there has been an increasing incidence of serious infections with antimicrobial-resistant Gram-negative bacilli [1][2][3][4][5] . These infections are becoming an important health-care issue, especially in intensive care units (ICUs) and hospitalized inpatients.…”
Section: Introductionmentioning
confidence: 99%
“…These infections are becoming an important health-care issue, especially in intensive care units (ICUs) and hospitalized inpatients. The most common organisms isolated are multidrugresistant (MDR) Pseudomonas aeruginosa, extendedspectrum beta-lactamase (ESBL)-producing and carbapenemase-producing Enterobacteriaceae and carbapenem-resistant Acinetobacter baumanii [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%